MODERATING EFFECT OF FIRM SIZE ON CAPITAL STRUCTURE DETERMINANTS: EVIDENCE FROM INDIAN FOOD PROCESSING INDUSTRY - Desai, Rajesh; Desai, Jay (Copernican Journal of Finance & Accounting, 2021)
Present research paper examines the determinants of capital structure decision of Indian food processing industry and assesses the moderating effect of firm size on this relationship. Using financial data of 40 firms for 10 years (2009–10 to 2018–19), panel least square regression analysis has been performed for data analysis. Based on regression results, the study concludes tangibility, tax rate, and cash flow as significant determinants of long-term borrowing for overall sample firms. On the other hand, tangibility, liquidity and profitability are significant factors affecting short-term borrowings of selected companies. Further, the study confirms that size of the firm moderates the effect of selected determinants on debt ratio of different categories of firms. It is, further, found that small size firms employ more debt with increasing profitability whereas medium and large size firms tend to reduce their debt levels with increasing profitability. The research findings will enhance understanding of capital structure determinants by probing the moderating impact of company size on it. The findings will be helpful to corporate managers in forming their borrowing strategies based on the relative size. Further, they can identify important factors to be considered while choosing debt or equity or in case of debt either short term or long term.